2018
DOI: 10.3389/fnbeh.2017.00253
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Remapping and Its Entorhinal Origin

Abstract: The activity of hippocampal cell ensembles is an accurate predictor of the position of an animal in its surrounding space. One key property of hippocampal cell ensembles is their ability to change in response to alterations in the surrounding environment, a phenomenon called remapping. In this review article, we present evidence for the distinct types of hippocampal remapping. The progressive divergence over time of cell ensembles active in different environments and the transition dynamics between pre-establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 84 publications
(138 reference statements)
3
67
0
Order By: Relevance
“…The changes in hippocampal spatial representations were the results of both the appearance and disappearance of place fields and the modulation of firing rate. These observations are consistent with the body of literature showing that changes in an environment (Kentros et al 1998;Anderson and Jeffery 2003), exposure to a different environment (Lever et al 2002;Leutgeb et al 2004Leutgeb et al , 2005 and spatial learning (Frank, Stanley, and Brown 2004;Karlsson and Frank 2008;Dupret et al 2010) induces a fast partial remapping of the spatial representation in the hippocampus (Anderson and Jeffery 2003), with the modulation of within-field firing rate (rate remapping) and the formation of new fields and disappearance of existing ones (global remapping) for different subgroups of neurons (Leutgeb et al 2004(Leutgeb et al , 2005Latuske et al 2018). Consistent with the accumulation of field activity on novel or changed goal locations (Fyhn et al 2002;Dupret et al 2010;Danielseon et al 2016) the ratio emerging fields / vanishing fields was highest at the home and reward locations.…”
Section: Discussionsupporting
confidence: 91%
“…The changes in hippocampal spatial representations were the results of both the appearance and disappearance of place fields and the modulation of firing rate. These observations are consistent with the body of literature showing that changes in an environment (Kentros et al 1998;Anderson and Jeffery 2003), exposure to a different environment (Lever et al 2002;Leutgeb et al 2004Leutgeb et al , 2005 and spatial learning (Frank, Stanley, and Brown 2004;Karlsson and Frank 2008;Dupret et al 2010) induces a fast partial remapping of the spatial representation in the hippocampus (Anderson and Jeffery 2003), with the modulation of within-field firing rate (rate remapping) and the formation of new fields and disappearance of existing ones (global remapping) for different subgroups of neurons (Leutgeb et al 2004(Leutgeb et al , 2005Latuske et al 2018). Consistent with the accumulation of field activity on novel or changed goal locations (Fyhn et al 2002;Dupret et al 2010;Danielseon et al 2016) the ratio emerging fields / vanishing fields was highest at the home and reward locations.…”
Section: Discussionsupporting
confidence: 91%
“…Real-time closed-loop replay content detection was activated in a subsequent rest epoch (REST) and in a second exposure to the radial maze (RUN2). The encoding model built using data from RUN1 was also valid for decoding the animal’s position in RUN2 ( Figure 1—figure supplement 3b ), indicating that recordings were stable and spatial representations had not remapped ( Anderson and Jeffery, 2003 ; Latuske et al, 2017 ). To evaluate the online detection performance without distortions of the signal, no actual feedback perturbation of brain activity was applied to the brain.…”
Section: Resultsmentioning
confidence: 96%
“…Previous studies have also reported that moderate PAE can reduce mGluR5 receptor function in DG (Galindo et al, 2004) and lead to elevated histamine H3 receptor-mediated inhibition of glutamate release from perforant path nerve terminals (Varaschin et al, 2018). Likewise, the integrity of input from the entorhinal cortex, which forms the most prominent source of perforant path axons, is critical for place cell activity (Latuske et al, 2018), and damage to entorhinal cortical cells can produce a similar loss of place field stability and reduction in spatial tuning (Hales et al, 2014;Schlesiger et al, 2018;Van Cauter et al, 2008).…”
Section: Discussionmentioning
confidence: 95%